Оцінювання якості вищої медичної освіти у контексті навчання іноземних студентів в Україні - Василь Гуменюк (Pavlo Tychyna Uman State Pedagogical University, 2013)
Проаналізовано зовнішній моніторинг і оцінювання якості вищої медичної освіти в Україні та за кордоном через міжнародні рейтингові шкали університетів. Визначено взаємозв'язок між якістю вищої освіти та привабливістю навчального закладу на ринку освітніх послуг, що забезпечує збільшення кількості іноземних студентів. The Ukrainian and international experience of assuring quality of training medical students has been demonstrated through international rating scales. Modern Ukraine has developed practice of grant of higher medical education for foreign students. Its substantial failing is that public organizations and professional medical associations don't control the questions of quality of preparation of specialists. The prospects of expansion of sphere of services for foreign students are in plane of two external systems of estimation of quality of medical education. First are the systems of external evaluation of quality of education in higher educational establishments. In different countries they have features and specifics, but generalization gives grounds to confirm stability and same purposefulness of the obligatory periodic monitoring of knowledge of all students. The successful drafting of tests is a condition for passing to the next stage of studies, or for the getting of professional qualification. Monitoring is performed by independent agencies, state or regional centers. Foreigners, which get the higher medical education, are subjected to the estimation of quality through: separate system of examinations for the foreign specialists of medical profile, which give a right on complete or limited medical practice; same examinations, which must be passed as by foreign applicants, as ukrainian students too. Ukraine has chosen exactly this way. The external monitoring of quality of knowledge of medical students (ukrainian and foreign) was founded in 1997-98 years. The second system is monitoring of quality after procedures of the world ratings of universities (Academic Ranking of of World Universities, ARWU) (Broad Subject Fields, ARWU-FIELD) and separate areas of knowledges (Subject Fields, ARWU-SUBJECT), in which the Ukrainian universities are not represented. From data of Webometrics on 03.01.2013 from Ukrainian medical higher establishments of education in the Internet most widely are presented Donetsk medical university - on 2021st place; 4394th - Bukovynian; 7246th - Lviv; 7812th - Odesa; 8309th - Lugansk; on 5970th place is placed Ukrainian medical stomatological academy. In subsequent there are needed to be researched the questions of decline of subjective effects in monitoring of quality of higher medical education in Ukraine, mechanisms of their comparison with the European standards of quality, development of ways of influence of indexes of the licensed examinations of specialists on their employment, which will allow to increase the rating of the Ukrainian universities, provide subsequent development of educational services on an export.